Synoptic Conditions and Moisture Sources for Extreme Snowfall Events Over East China. Issue 2 (22nd January 2019) - Yang, Zifan; Huang, Wenyu; He, Xinsheng; Wang, Yong; Qiu, Tianpei; Wright, Jonathon S.; Wang, Bin
Abstract: The favorable circulation pattern and moisture sources for wintertime extreme snowfall events over East China during 1979–2017 are explored. A coupling between a Rossby wave train along the subtropical jet stream (i.e., the circumglobal teleconnection) and central Siberian blocking activities plays a leading role in triggering these events. This coupling leads to the formation of cyclonic anomalies, strong southwesterly winds, large‐scale moisture convergence, and powerful updrafts over East China, all of which prompt the occurrence of precipitation. The central Siberian blocking activities increase the fraction of the precipitation that falls as snowfall through enhancing cold air intrusion into East China. An Eulerian moisture budget analysis reveals that moisture fluxes across the southern and western boundaries of the East China region provide the moisture for the precipitation during the extreme snowfall events, while the increase in the precipitable water helps extend the duration of these events. The geographic distributions of the evaporative moisture sources for both the snowfall and rainfall during these extreme events are estimated using a Lagrangian approach. This analysis reveals that the major moisture sources for snowfall originate from land areas, while those for the rainfall originate from sea areas. In addition, local moisture recycling over East China provides a remarkably higher relative contribution to snowfall than it does to rainfall. The identification of the synoptic conditions and moisture sources not only improves our understanding of the formation of extreme snowfall events over East China but also provides forecast guidance for extreme snow disasters. Key Points: The coupling of the circumglobal teleconnection and central Siberian blocking activities is critical to East China extreme snowfall events Central Siberian blocking activities favor a considerable part of the precipitation over East China occurring as snowfall Local moisture recycling plays a leading role in providing the evaporative moisture sources for extreme snowfall events